Gender, Women’s Barriers and Innovation in Agriculture: A Systemic Literature Review - Dabkienė Vida (European Countryside)
Agricultural innovations, coupled with the pivotal role of women in their implementation, are increasingly recognized as essential for advancing sustainable agricultural practices and contributing to the achievement of the Sustainable Development Goals. The article provides a systematic literature review (SLR) on gender women’s barriers and innovation in agriculture. To achieve this, scientific publications based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was conducted. This paper reviews 539 articles in the ISI Web of Science. The SLR analysis allowed the identification of several key literature nodes such as the most cited articles, the most productive countries, and the most popular keywords. The analysis of the five most-cited articles authored by researchers affiliated with European institutions, along with a review of relevant research from European countries, reveals limited attention to the research field within the European context. Research points to persistent barriers for women in agriculture, including social norms, gender stereotypes, and structural inequalities, which hinder access to resources and leadership. These challenges are evident in both developing and developed countries, reflecting slow progress in addressing gender disparities globally.